2015
DOI: 10.1159/000441486
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of S-1 for Previously Untreated Elderly Patients with Advanced Non-Small Cell Lung Cancer

Abstract: Background: S-1, a novel oral fluoropyrimidine, is active in the treatment of non-small cell lung cancer (NSCLC). However, data on S-1 for elderly patients with NSCLC are insufficient. Methods: Eligibility criteria were no prior chemotherapy, stage IIIB or IV NSCLC, performance status 0-1, age >70 years, and adequate hematological, hepatic, and renal functions. Patients received S-1 (40 mg/m2 twice a day) for 28 consecutive days. This schedule was repeated every 6 weeks. The primary end point was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…It was presumed that one of the mechanisms of crossresistance between PEM and S-1 was reduction of TS expression due to prior PEM treatment. To compare this study, previous reports about S-1 monotherapy were checked up (Table 3) (7,(9)(10)(11)(12)(13)(14). Interestingly, in two studies about e cacy of S-1 whose registration period was prior to 2009, S-1 showed higher ORR in adenocarcinoma or non-SQ than in squamous cell carcinoma (11,12).…”
Section: Discussionmentioning
confidence: 96%
“…It was presumed that one of the mechanisms of crossresistance between PEM and S-1 was reduction of TS expression due to prior PEM treatment. To compare this study, previous reports about S-1 monotherapy were checked up (Table 3) (7,(9)(10)(11)(12)(13)(14). Interestingly, in two studies about e cacy of S-1 whose registration period was prior to 2009, S-1 showed higher ORR in adenocarcinoma or non-SQ than in squamous cell carcinoma (11,12).…”
Section: Discussionmentioning
confidence: 96%
“…S-1 is a newer drug in the same class, combining fluoropyrimidines and DPD inhibition. Its single-agent response rate against advanced NSCLC exceeds 20% [13][14][15] versus less than 10% in UFT. 8,9 In fact, postoperative adjuvant therapy with S-1 was reported to be superior to UFT with respect to RFS in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These regimens combine cisplatin or carboplatin with cytotoxic drugs such as paclitaxel, docetaxel, gemcitabine, vinorelbine, and pemetrexed [ 37 ]. Cyclophosphamide [ 38 ], S-1 [ 39 ], and etoposide [ 40 ] are also treatment approaches for advanced NSCLC. However, many factors affect the curative potential of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%